Nitric oxide, endothelin-1, and superoxide production in arterial bypass grafts - (:unkn) unknown (TEXAS HEART INST, 2006)
In this study basal and thrombin-stimulated release of nitric oxide and endothelin-1 in the internal mammary artery and the radial artery were measured, together with superoxide radicals generated after anoxia and reoxygenation. Arterial segments were obtained from patients undergoing coronary bypass operations. Quantification of nitric oxide was performed by measuring the stable oxidation products of nitric oxide. Endothelin levels were measured by an enzyme immunoassay kit and the superoxides were measured by lucigenin-enhanced chemiluminescence. Basal and stimulated release of nitric oxide from the Internal mammary artery is significantly higher than that in the radial artery On the other hand, basal release of endothelin-1 is less in the internal mammary artery than in the radial artery, but similar after stimulation. In our study the quantity of superoxide radicals produced by the internal mammary artery was greater than that produced by the radial artery. Our results show that there are differences between these 2 arteries in regard to production of nitric oxide, endothelin-1, and superoxide radicals. These differences may have a role in the process of atherogenesis and may contribute to long-term patency of arterial bypass grafts. These results may also explain the mechanism of radial artery graft spasm in coronary artery surgery and may constitute a basis for future pharmacological and clinical improvements for successful surgical application.
Keywords: endothelin; internal mammary artery; nitric oxide; radial artery; superoxide; INTERNAL MAMMARY ARTERIES; HUMAN BLOOD-VESSELS; ACTIVATED PROTEIN-KINASES; SMOOTH-MUSCLE-CELLS; RADIAL ARTERY; RISK-FACTORS; THROMBIN; RELEASE